Dual Monetary System: A Systematic Review Using Bibliometric Analysis - Ririn Riani (Journal of Islamic Economics Literatures, 2021)
Islamic economy grows in Muslim-majority countries within the monetary system, although the monetary system dominates with central banks and paper money. As a result, the Islamic monetary system developed its regulations and transmission mechanisms. The central bank must implement policies of both conventional and Islamic banking systems. From an Islamic point of view, the monetary policy effectively extends overall macroeconomic conditions in countries with multiple financial systems. Bibliometric studies in research related to the development of Dual Monetary System trends published by leading journals from 1974 to 2021, indexed by Scopus. Analysis of keyword trends, authors, and institutions. The data analyzed were 77 research publications using descriptive statistical methods and bibliometric analysis. The results show that the number of articles discussing the theme of the Dual Monetary System has an increasing trend from year to year, in line with the development of the Islamic economy. The most popular keywords used are monetary policy, dual banking system, and credit channels. The most prolific writer is Majid M.S.A. Meanwhile, the country with the most famous authors in the United States. This research provides information for researchers who focus on research in the field of the Monetary System. In the end, this theme is likely to continue to be developed.